A Back and Forth Journey. Dialogues between Alejandro Joseph de Guelle and James Cook - Cervera Molina, Ana E. (2020)
The 18th century was a complicated time in Central American history. In Europe, England and Spain were involved in a long war for control of American territories. Consequently, the two countries signed controversial pacts in the royal courts. The limited space located between the western part of the Yucatán Peninsula and what is now northern Belize was disputed territory. This dispute was exemplified by two remarkable political actors: Alejandro Joseph de Guelle and James Cook. Both men traveled back and forth throughout the territory and contributed to building a space in our imagination for such a historical borderland.